2019
DOI: 10.7759/cureus.5270
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Oil and Iodine-125 Brachytherapy for Uveal Melanoma in High-Risk Patients

Abstract: PurposeSilicone oil a burgeoning adjuvant in the treatment of uveal melanoma where it is used for tissue protection during I-125 brachytherapy. While risk factors in the development of radiation retinopathy (RR) have been identified, treatment modulation for high-risk patients has largely been overlooked. We seek to expand the literature on this subject by reporting outcomes of I-125 brachytherapy with silicone oil in a high-risk population in the community setting.MethodsFive patients with uveal melanoma and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…This practice is based on the evidence of an attenuating effect of silicone oil 1000-cSt, resulting in a reduction of 50–60% of radiation exposure of healthy ocular tissue to side radiation from iodine-125 brachytherapy [ 20 ]. Lyons et al [ 21 ] reported 2 cases of RR and 1 case of NVG that was eventually enucleated. BCVA was particularly well preserved in the cohort.…”
Section: Resultsmentioning
confidence: 99%
“…This practice is based on the evidence of an attenuating effect of silicone oil 1000-cSt, resulting in a reduction of 50–60% of radiation exposure of healthy ocular tissue to side radiation from iodine-125 brachytherapy [ 20 ]. Lyons et al [ 21 ] reported 2 cases of RR and 1 case of NVG that was eventually enucleated. BCVA was particularly well preserved in the cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Bearing in mind the limitations mentioned above and comparing the research studies on visual acuity deterioration after Ru-106 brachytherapy, I-125 brachytherapy and proton beam therapy of uveal melanoma published at the turn of the 20th and 21st centuries [ 3 , 30 , 55 , 56 ] and in the last 4 years [ 9 , 11 , 21 , 31 , 33 , 34 , 35 , 37 , 38 , 39 , 41 , 42 , 44 , 49 , 50 , 51 ], we can conclude that the degree of visual impairment is comparable. Considering the extremely dynamic development of medicine and widely understood technology, one would like to achieve greater progress in this field.…”
Section: Discussionmentioning
confidence: 99%
“…A method of protecting healthy tissues in the form of replacing the vitreous body with silicone oil proposed by Yang et al, Lyons et al and other researchers suggests that further searching for substances that protect against radiation even better and, at the same time, are safer for the eye is needed [ 47 , 48 , 49 , 50 ]. However, serious potential complications associated with the vitrectomy procedure should be borne in mind when considering such a method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation